Climate station data from the Kuujjuaq region in Nunavik, Quebec, Canada ... : Données des stations climatiques de la région de Kuujjuaq au Nunavik, Québec, Canada ... - Sarrazin, Denis; Allard, Michel (Nordicana D, 2024)
The data are from the Kuujjuaq region in Nunavik, Quebec, Canada. It contains data from air temperatures. The available datasets cover the period from 2006-2021. Data are available as: (1) recorded data; (2) daily averages; (3) monthly averages; and (4) yearly averages. ... : Les données proviennent de la région de Kuujjuaq au Nunavik, Québec, Canada. On y retrouve des données de température de l'air. La période couverte par les données est 2006-2021. Les données sont disponibles en quatre formats: (1) données enregistrées; (2) la moyennne journalière; (3) la moyenne mensuelle et (4) la moyenne annuelle. ...